Remembering Bulldog Turner : Unsung Monster of the Midway - Barr, Michael D., 1952- (Book collections on Project MUSE., 2013)
"Clyde "Bulldog" Turner rose from the West Texas plains to become an early lynchpin of the Chicago Bears and the NFL and one of the greatest linemen of the pre-television era. Fame, however, did not stick to Bulldog Turner because the positions he played rarely made headlines. Bulldog played center and linebacker, while the recognition, glory, and money went to those who scored touchdowns. Like Pudge Heffelfinger, Fats Henry, Ox Emerson, George Trafton, Bruiser Kinard, Adolph Shultz, or Mel Hein, Bulldog Turner is a ghostly character from football's leather helmet days. Still, no man played his positions better than Bulldog Turner. He was the ideal combination of size and speed, and every coach's dream: a lineman who could block like a bulldozer, run like a halfback, and catch like a receiver. Despite his talents, Bulldog never made much money playing football, and what he did earn slipped through his fingers like sand. When he retired, his iconic nickname faded from memory. He died in relative obscurity on what remained of his Texas ranch. Remembering Bulldog Turner brings an NFL great into the limelight he never enjoyed as a football player."--